2014
DOI: 10.1155/2014/157895
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of Virus Infectivity by Antibodies: Old Problems in New Perspectives

Abstract: Neutralizing antibodies (NAbs) can be both sufficient and necessary for protection against viral infections, although they sometimes act in concert with cellular immunity. Successful vaccines against viruses induce NAbs but vaccine candidates against some major viral pathogens, including HIV-1, have failed to induce potent and effective such responses. Theories of how antibodies neutralize virus infectivity have been formulated and experimentally tested since the 1930s; and controversies about the mechanistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
213
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(220 citation statements)
references
References 220 publications
(371 reference statements)
3
213
0
4
Order By: Relevance
“…While virus neutralization assays measure a functional subset of antibodies and provide an important indicator of antiviral immunity, the best correlate of protection against viremia in DENV infection may be total polyclonal antibody titers, rather than neutralizing antibody titers (43). Antibodies that are weakly neutralizing in cell culture assays can contribute to physiologically important non-ADE mechanisms of virus clearance that are facilitated by receptor-mediated uptake and effector cells (48).…”
Section: Discussionmentioning
confidence: 99%
“…While virus neutralization assays measure a functional subset of antibodies and provide an important indicator of antiviral immunity, the best correlate of protection against viremia in DENV infection may be total polyclonal antibody titers, rather than neutralizing antibody titers (43). Antibodies that are weakly neutralizing in cell culture assays can contribute to physiologically important non-ADE mechanisms of virus clearance that are facilitated by receptor-mediated uptake and effector cells (48).…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination against viral infections confers protection by generating neutralizing antibodies [24]. Since antibody production is crucial for the prevention of viral infections, we have shown that SCE300ET when administered along with Rb antigen, significantly enhanced the RVNA titres and the antibody titers were found to be higher as compared to Algel and rabies antigen immunized mice.…”
Section: Discussionmentioning
confidence: 88%
“…Klasse: "Neutralization [….] is defined as the reduction in viral infectivity by the binding of antibodies to the surface of viral particles (virions), thereby blocking a step in the viral replication cycle that precedes virally encoded transcription or synthesis" (Klasse, 2014).…”
Section: Trim21 Effector Mechanismmentioning
confidence: 99%